Novel virus-encoded microRNA molecules expressed by ovine herpesvirus 2-immortalized bovine T-cells - Levy, Claire S.; Hopkins, John; Russell, George C.; Dalziel, Robert G. (Journal of General Virology, 2012)
A number of herpesviruses have now been shown to encode microRNAs (miRNAs) that have roles in control of both viral and cellular gene expression. Ovine herpesvirus 2 (OvHV-2) is the causative agent of sheep-associated malignant catarrhal fever, a fatal lymphoproliferative disease of cattle. Using massively parallel sequencing and Northern hybridization we have identified eight putative miRNAs encoded by OvHV-2 expressed in an OvHV-2-immortalized bovine lymphocyte cell line. These eight miRNAs are encoded in two areas of the OvHV-2 genome that contain no predicted protein coding regions and show no sequence similarity with other herpesvirus or cellular miRNAs. This represents the first report of the expression of virally encoded miRNAs in the genus Macavirus of herpesviruses.